Changes in various forms of fibronectin in patients undergoing coronary artery bypass grafting with cardiopulmonary bypass – a prospective, observational study - Anna Lemańska-Perek; Dorota Krzyżanowska-Gołąb; Grzegorz Wysoczański; Barbara Barteczko-Grajek; Waldemar Goździk; Barbara Adamik (Scientific Reports)
Abstract Coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB) is associated with the transient activation of a systemic inflammatory response. Fibronectin (FN), an endogenous inflammatory mediator, is a key component of the extracellular matrix. This study aimed to detect changes in cellular and plasma FN levels, as well as its potential fragmentation or FN-fibrin complex formation, in 40 patients undergoing CABG with CPB. Our results indicate that CPB was associated with changes in the levels of cellular and plasma FN and with intensified FN fragmentation. Moreover, FN-fibrin complexes were detected in all patients, indicating activation of the coagulation process during CPB. In a multivariate regression analysis, a history of arterial hypertension and CPB duration influenced plasma FN levels at 6 h (β = -0.458, p = 0.001; -0.375, p = 0.008, respectively) and 12 h (β = -0.293, p = 0.026; -0.554, p = 0.000) after surgery. Alterations in FN concentration, intensified FN degradation, and the presence of FN-fibrin complexes after surgery may suggest that these changes are related to the remodelling of the extracellular matrix resulting from cardiac surgery and the associated repair processes. The results indicate that FN has clinical potential as a marker of repair processes.